Neurological soft signs in Mazahua children with severe malnutrition and anemia - Álvarez-Izazaga, Marsela Alejandra (2020)
Short stature is a sign of chronic malnutrition. It occurs in individuals who usually live in poverty, such as the case of rural communities and indigenous people of Mexico (Muñoz & Chávez, 2007). This condition is detrimental for neuropsychological development and is associated with the presence of neurological soft signs. Therefore, the purpose of this cross-sectional field study was to explore whether a group of indigenous Mazahua children with early malnutrition show neurological soft signs. The study was conducted in two rural communities at the Mazahua region in the State of Mexico. The participants were 36 children aged 6 to 10 with severe malnutrition andanemia. They were selected using a non-probabilistic intentional quota sampling. They were assessed with the Neurological Soft Signs Scale (SNB-MX) proposed by Salvador-Cruz et al. (2018). Regardless of the age, the results showed significant associations between malnutrition and left-right identification, attention, executive functions and working memory. This study contributes to understanding the specific impact of early severe malnutrition and anemia in Mazahua indigenous children.